IOT connected predictive vehicle systems - ., Murugadass; Sheela Gowr, P; Latha, M; V. Anbazhagu, U (International Journal of Engineering and Technology, 2018)
Predictive maintenance is to identify vehicle maintenance issues before they occur. By leveraging data from navigation locator and motion of vehicle, status and parts of the vehicle, requirement of service, warranty repairs with current vehicle sensor data would be difficult for a human to discover. Predictive data analytics can find meaningful correlations via Connected Vehicle which is a technological advancement in Automobile industry. Using Internet of Things IOT, various information like health information of a driving person and navigation of vehicle can be easily monitored. Connected vehicle deals with cars and other vehicles where we the data will be shared with the backed applications like micro services.Â